2013
DOI: 10.1016/j.neubiorev.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Moment-to-moment brain signal variability: A next frontier in human brain mapping?

Abstract: Neuroscientists have long observed that brain activity is naturally variable from moment-to-moment, but neuroimaging research has largely ignored the potential importance of this phenomenon. An emerging research focus on within-person brain signal variability is providing novel insights, and offering highly predictive, complementary, and even orthogonal views of brain function in relation to human lifespan development, cognitive performance, and various clinical conditions. As a result, brain signal variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
470
5
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 493 publications
(535 citation statements)
references
References 147 publications
32
470
5
5
Order By: Relevance
“…To the extent that pharmacological DA studies suffer from the file drawer problem (43), drug administration order may be one culprit in zeroing out inverse behavioral/brain effects resulting from session order. In the present study, this inversion was reflected in RT-SD BOLD relations, serving as a springboard for future work seeking to elucidate the state-and practice-dependent neurochemical basis of brain signal dynamics and its developmental and cognitive correlates (2). All participants were righthanded, with normal or corrected-to-normal vision, and reported to be psychiatrically and neurologically healthy.…”
Section: Amph-related Relations Between Sd Bold and Wm Performance As Amentioning
confidence: 76%
See 3 more Smart Citations
“…To the extent that pharmacological DA studies suffer from the file drawer problem (43), drug administration order may be one culprit in zeroing out inverse behavioral/brain effects resulting from session order. In the present study, this inversion was reflected in RT-SD BOLD relations, serving as a springboard for future work seeking to elucidate the state-and practice-dependent neurochemical basis of brain signal dynamics and its developmental and cognitive correlates (2). All participants were righthanded, with normal or corrected-to-normal vision, and reported to be psychiatrically and neurologically healthy.…”
Section: Amph-related Relations Between Sd Bold and Wm Performance As Amentioning
confidence: 76%
“…As predicted, AMPH boosted low BOLD signal variability levels in older adults across conditions. Given increasing evidence of higher overall SD BOLD levels in young, high performers in previous work (2,(5)(6)(7)30), we assumed the average YA to begin (at placebo) nearer to optimal signal variability levels, and that the average OA would rise toward YA levels. Accordingly, individual slopes revealed that the majority of OA increased in SD BOLD on AMPH (especially those with the lowest levels of SD BOLD at placebo), whereas YA showed a mix of positive and negative slopes (resulting in a net zero group change).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to functional connectivity, amplitude of low-frequency fluctuation (ALFF) is a metric that measures the fluctuation amplitude of each single voxel (Liu et al, 2013;Zang et al, 2007;Zou et al, 2008;Zuo and Xing, 2014) and could be applied to both BOLD and ASL techniques. ALFF has been widely used to examine moment-to-moment brain signal variability (Garrett et al, 2011;Garrett et al, 2013), to correlate with task activations and behavior , and to characterize disease stages (Han et al, 2011;Lui et al, 2009;Wang et al, 2011b;Yu et al, 2014). Direct comparison of the short-and long-term test-retest reliability of BOLD and CBF contrasts on an identical group of subjects at single voxel level is still lacking.…”
Section: Introductionmentioning
confidence: 99%